Understanding what women want: eliciting preference for delivery health facility in a rural subcounty in Kenya, a discrete choice experiment - Jackline Oluoch-Aridi; Francis Wafula; Mary B Adam (BMJ Open)
Objective To identify what women want in a delivery health facility and how they rank the attributes that influence the choice of a place of delivery.Design A discrete choice experiment (DCE) was conducted to elicit rural women’s preferences for choice of delivery health facility. Data were analysed using a conditional logit model to evaluate the relative importance of the selected attributes. A mixed multinomial model evaluated how interactions with sociodemographic variables influence the choice of the selected attributes.Setting Six health facilities in a rural subcounty.Participants Women aged 18–49 years who had delivered within 6 weeks.Primary outcome The DCE required women to select from hypothetical health facility A or B or opt-out alternative.Results A total of 474 participants were sampled, 466 participants completed the survey (response rate 98%). The attribute with the strongest association with health facility preference was having a kind and supportive healthcare worker (β=1.184, p<0.001), second availability of medical equipment and drug supplies (β=1.073, p<0.001) and third quality of clinical services (β=0.826, p<0.001). Distance, availability of referral services and costs were ranked fourth, fifth and sixth, respectively (β=0.457, p<0.001; β=0.266, p<0.001; and β=0.000018, p<0.001). The opt-out alternative ranked last suggesting a disutility for home delivery (β=−0.849, p<0.001).Conclusion The most highly valued attribute was a process indicator of quality of care followed by technical indicators. Policymakers need to consider women’s preferences to inform strategies that are person centred and lead to improvements in quality of care during delivery.